2017
DOI: 10.22616/foodbalt.2017.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrogen peroxide, ozonised water and NATURESEAL® AS5 solution on the microbiological parameters of fresh-cut carrot

Abstract: Innovative (ozonised water, hydrogen peroxide) treatment solutions is one of the newest treatment agents used to decrease the count of microorganisms in vegetables. NatureSeal ® AS5 is a commercial solution used for the treatment of vegetables worldwide. The aim of this work was to study the effect of the various treatment solutions -hydrogen peroxide, ozonised water and NatureSeal ® AS5 (in various concentrations and for different treatment time) with the main purpose to ensure the microbiological safety of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Among these scientific publications, two authors applied ozone after a first washing with tap water in two different conditions: spraying ozonated water for 2 min [ 78 ] or on a bed reactor inside a chamber [ 62 ]. In the other works, ozonated water was prepared in a reservoir by circulating potable tap water or deionized water through an ozone generator using oxygen or air as feed gas [ 79 , 80 ] or by bubbling ozone gas into water [ 72 , 74 , 76 ]. In these cases, the indicated concentrations are those measured by the analyzer at the end of the preparation of the washing water and before the step of the treatment beginning [ 72 , 76 , 79 ].…”
Section: Effects Of Ozone Treatment On Carrot Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Among these scientific publications, two authors applied ozone after a first washing with tap water in two different conditions: spraying ozonated water for 2 min [ 78 ] or on a bed reactor inside a chamber [ 62 ]. In the other works, ozonated water was prepared in a reservoir by circulating potable tap water or deionized water through an ozone generator using oxygen or air as feed gas [ 79 , 80 ] or by bubbling ozone gas into water [ 72 , 74 , 76 ]. In these cases, the indicated concentrations are those measured by the analyzer at the end of the preparation of the washing water and before the step of the treatment beginning [ 72 , 76 , 79 ].…”
Section: Effects Of Ozone Treatment On Carrot Qualitymentioning
confidence: 99%
“…Secondly, concerning microbiological quality, all tested liquid ozone treatments achieved a significant reduction in total mesophilic aerobic bacteria [ 64 , 76 , 79 , 80 ], yeasts and molds [ 64 , 79 , 80 ], coliforms [ 64 ], E. coli [ 62 , 64 , 72 ], and Salmonella enteridis [ 64 ].…”
Section: Effects Of Ozone Treatment On Carrot Qualitymentioning
confidence: 99%
“…For example, NatureSeal products are patented pre-cise blends of GRAS (Generally Recognized as Safe) vitamins and minerals that inhibit browning while maintaining flavor and texture and extending the shelf life of freshcut produce (www.natureseal.com). The products have been reported to preserve the texture, flavor, appearance, crispness, and color of fresh-cut fruits at low but abovefreezing temperatures (Roessle et al 2009;Augspole et al 2017;Alicea et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Researcher Abubake (2006) described that application of NatureSeal TM agents is a popular approach for prevention enzymatic browning in fresh-cut vegetables. In her study Augspole et al (2017) showed that NatureSeal ® AS5 water solution has antimicrobial activity, thus it may be possible that it has a essential effect on the microbiological quality of fresh-cut carrots during storage. Therefore, the aim of the research was to investigate microbiological quality changes of shredded carrots treated with NatureSeal ® AS5 during storage in several packaging materials.…”
Section: Introductionmentioning
confidence: 99%
“…Abubakr (2016) in his study has shown that NatureSeal ® AS1 and NatureSeal ® AS5 products can reduce browning in fresh cut fruit slice. Many authors (Augspole et al, 2017;Saha et al, 2009;Rösßle et al, 2009) in their studies emphasize that the NatureSeal TM is a calcium ascorbate powder used in the food industry. Asrey et al (2008) in their studies described that NatureSeal ® AS5 is the first antioxidant product of its kind, which doesn't have a bad aftertaste or product residue.…”
Section: Introductionmentioning
confidence: 99%